Revitalisasi Kesadaran Masyarakat dalam Pemilahan Sampah melalui Edukasi Lingkungan di Desa Karangtawar, Kabupaten Lamongan - Rahmah Arfiyah Ula; Fita Fitriatul Wahidah; Lilik Erviani; Merinda Nur Indahsari; Sitti Nur Ilmiah; Muhammad Subhan (Lembaga Pengembangan Kinerja Dosen, 2026)
Waste management issues remain an environmental challenge that requires active community involvement, particularly in the practice of waste sorting from the source. Although the community has received education regarding waste management, consistency in implementing waste sorting behavior often declines over time. This community service activity aims to revitalize awareness and reinforce community behavior in conducting waste sorting in Karangtawar Village, Lamongan Regency. The activity was carried out on August 25, 2023, involving 26 participants consisting of youth organization members, village officials, and PKK members. The method used was an educational-participatory approach through counseling, waste sorting demonstrations, and interactive discussions. Data were collected through observation, documentation, and field notes, and then analyzed descriptively in a qualitative manner. The results of the activity indicate high participation and enthusiasm from the participants throughout the event. Participants were able to understand the differences between organic, inorganic, and recyclable waste, and demonstrated increased awareness of the importance of waste sorting. As a follow-up, separated waste bins were provided to support the implementation of waste sorting behavior within the community. Nevertheless, the sustainability of waste sorting behavior still requires ongoing guidance and reinforcement. This activity demonstrates that an educational-participatory approach is effective in enhancing public understanding and awareness of sustainable waste management.